A wedding in springtime - Forester, Amanda (Sourcebooks Casablanca, 2013)
"Her timing couldn't be worse-- Miss Eugenia Talbot's presentation to the queen is spoiled by a serious faux pas -- the despicable William Grant made her laugh, right in front of Her Majesty. Now Eugenia is ruined and had better marry--someone, anyone--at once. And his couldn't be better--Roguish William Grant has never taken anything seriously in his life. Until he meets Eugenia Talbot, who makes him feel and do things he never thought he would."--back cover.